The conservation of pedunculate oak (Quercus robur) stands in the territory of Parco Lombardo Valle del Ticino (province of Milano and Pavia): main results and management proposals after three years of testing - Bianchi L; Caronni F; Giovannini G; Paci M (Forest@, 2013)
The conservation of pedunculate oak (Quercus robur) stands in the territory of Parco Lombardo Valle del Ticino (province of Milano and Pavia): main results and management proposals after three years of testing.. In the territory of “Parco Lombardo della Valle del Ticino” an experiment, aimed to assess the silviculture pattern suitable for the conservation of stands dominated by peduncolate oak, was set up in 2008. Four experimental areas were located, both in “meso-hygrophilous” and “mesophilous” sites, respectively corresponding to: (a): less intense seed felling; (b): more intense seed felling (both of them aimed to promote the natural regeneration); (c): opening of gap (800 m2) followed by artificial regeneration (both protected and non-protected by shelters); (d): control. Three years after the set up of the experiment, the main results may be summarized as follows: (i): both the seed fellings (the more and the less intense felling) produced a process of natural regeneration, at present insufficient to ensure the continuity of the forest canopy cover; (ii): the branchwood released after utilization produced a positive effect on settlement and growth of peduncolate oak seedlings, attributable to the protection both from the roe deer browsing and wild boar acorn consumption; (iii): ventilated shelters (Tubex Ventex®) produced a positive effect on planting stock, both in terms of survival and growth; (iv): monitoring over time, especially as regards the analysis of the effects of different types of treatment on the processes of regeneration, can provide indications management extensible in similar populations in the territory of the Parco Lombardo Valle del Ticino.